Improving resilience in times of multiple crisis - Andreas Pinkwart; Gideon Schingen; Anna-Tina Pannes; Dirk Schlotböller (Schmalenbach Journal of Business Research (SBUR), 2022)
Due to the trend towards more frequent and multiple crises, it is essential for enterprises as well as for states and entire economic areas to develop strategies to improve resilience. In this article, existing challenges and conceivable strategies for improving resilience will be outlined from a microeconomic as well as from a macroeconomic perspective. To mitigate vulnerabilities of Supply Chains in the last decades, drivers for improving Supply Chain resilience have been explored. They are presented as contributing to building resilience on the micro level. On the macro level, opportunities and limits of current approaches for strategic independence are discussed. In terms of a new regulatory policy, a rescue of honour for global cooperation and free trade is proposed by the authors.
Keywords: 650